2006
DOI: 10.1159/000095562
|View full text |Cite
|
Sign up to set email alerts
|

Activated mTOR and PKR Kinases in Lymphocytes Correlate with Memory and Cognitive Decline in Alzheimer’s Disease

Abstract: Background: The control of translation, involving the kinases mTOR (mammalian target of rapamycin) and PKR (double-stranded RNA-dependent protein kinase), modulates cell survival and death and is altered in the brains of patients with Alzheimer’s disease (AD). In AD increased susceptibility of lymphocytes to apoptosis has been reported. Methods: We investigated the level of the kinases mTOR and PKR and the eukaryotic initiation factor 2α (eIF2α) in lymphocytes of patients with AD in comparison with controls. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 52 publications
(37 reference statements)
4
59
0
1
Order By: Relevance
“…Expression of cytosolic PrP C has also been shown to activate PKR (39), and neuronal immunostaining for activated PKR has been found in cases of Creuztfeldt-Jakob disease (40). Interestingly, phosphorylated PKR is also a marker for cognitive decline in individuals with Alzheimer's disease (41) and, in cultured neurons, PKR activation and eIF2α phosphorylation play a role in the induction of apoptosis by β-amyloid peptides (42).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of cytosolic PrP C has also been shown to activate PKR (39), and neuronal immunostaining for activated PKR has been found in cases of Creuztfeldt-Jakob disease (40). Interestingly, phosphorylated PKR is also a marker for cognitive decline in individuals with Alzheimer's disease (41) and, in cultured neurons, PKR activation and eIF2α phosphorylation play a role in the induction of apoptosis by β-amyloid peptides (42).…”
Section: Discussionmentioning
confidence: 99%
“…We also found that activation of PKR and eIF2 ␣ is crucial in ␤ -amyloid (A ␤ )-induced apoptosis in cultured cortical neurons [38] , where extracellular accumulation of A ␤ peptides is a key pathological hallmark of AD [39] . In a recent study, the levels of phospho-PKR and phospho-eIF2 ␣ have been found to be elevated in lymphocytes of AD patients, and these changes were significantly correlated with the cognitive and memory test scores [40] .…”
Section: Pkr and Neurodegenerative Diseasesmentioning
confidence: 94%
“…Loss of mTOR impairs the reconsolidation phase of traumatic memory (98). In patients with AD, a decrease in mTOR activity in peripheral lymphocytes appears to correlate with the progression of AD (99). Loss of mTOR signaling also has been shown to impair long-term potentiation and synaptic plasticity in animal models of AD that can be restored through the upregulation of mTOR signaling (100).…”
Section: Mtor In Memory and Alzheimer’s Diseasementioning
confidence: 99%